Effects Of Government Expenditure, Fiscal Policy And Institutions On The Economic Growth Of Asian Economies - Abdullah, Hussin (2008)

(untitled)
This study determines the long run relationship between government expenditure, fiscal policy and economic growth, the role of institutions on economic growth, and whether institutions require complimentary factors to influence economic growth through an interaction term effects between government expenditure and institutions, and fiscal policy and institutions on economic growth of thirteen Asian economies. It is particularly important because economic growth has declined and become stagnant significantly and government expenditure does not inhibit the full exploitation of the growth potential of Asian economies. There is also a broad consensus that the developments in fiscal policies contribute to the relatively weak growth performance. Weak fiscal positions have left little room for further fiscal expansion in most Asian economies when faced by economic slowdown. Generally efficiency of the role of institutions is sadly lacking, and there are numerous deficiencies in the functioning of role of institutions in Asian countries. We formulated a simple growth model which is based on the augmented version of the Solow model in a sample of thirteen Asian countries as case studies using recently developed panel cointegration methods; FMOLS introduced by Pedroni (1996, 2000 and 2001) and GMM estimators developed for dynamic models of panel data, introduced by Arellano and Bond (1991) and Blundell and Bond (1998). The findings indicate that there is a positive and negative coefficient and significant long run relationship between government expenditure, fiscal policy and economic growth. The results of institutions and interaction term indicate that there is a role of institutions and the institutions require complimentary factors to influence economic growth through an interaction term effects. The findings also indicate that initial real per capita GDP, saving in physical capital (investment) and population growth rate are in line with Solow model which is the negative coefficient on initial GDP as in most published growth regressions is interpreted as conditional convergence while investment and population growth are positive and negative, respectively. Several important conclusions can be drawn from the study. Government policies and institutions seem to play an important role and attract investment are correlated with higher growth. It is also possible to account for plausible interactions drawing upon research from various disciplines in social sciences. It can be hoped that models built using an interdisciplinary approach can better account for observed variation in the data.